Dyplomacja polska wobec Międzynarodowego Instytutu Kinematografii Edukacyjnej Ligi Narodów (1928–1937) - Brzeziński, Andrzej Maciej (Przegląd Nauk Historycznych, 2008)
In 1928 the Polish Diplomacy accepted the Italian initiative of establishing International Institute of the Educational Cinema of the League of Nations (IIEC) in Rome. The IIEC was founded as the center of information concerning the various problems of educational cinema. The principal object of the Rome Institute was to encourage the production and to promote the distribution and exchange of educational films. The decision of Polish Foreign Ministry to support the IIEC was motivated by political reasons of maintaining good relations with Italy and underlying the Polish interest in the international intellectual cooperation of the League of Nations. In 1930 the Polish subsidy of 30 000 L facilitated the nomination Poland's representative at the IIEC. The Polish Diplomacy was interested in the Convention of October 11th 1933 for facilitating the international circulation of films of an educational character, initiated by IIEC. Poland signed Convention but reserved her rights to protect the home production of educational films. In the next years Polish authorities abstained from the ratification this Convention. In 1935 the Polish Diplomacy has taken negative position towards the lICE. Since this year, especially during Italian aggression against Abyssinia, the Rome Institute was exploited by fascist Diplomacy in the foreign policy and propaganda. In 1936 the Polish Foreign Ministry discontinued to subsidize the lICE. Mter withdrawal Italy from the League of Nations on December 11th 1937, the lICE was closed down on December 31st 1937.